The Albumin in Acute Stroke (ALIAS) Multicenter Clinical Trial: Safety Analysis of Part 1 and Rationale and Design of Part 2 - Ginsberg, Myron D.; Palesch, Yuko Y.; Martin, Renee H.; Hill, Michael D.; Moy, Claudia S.; Waldman, Bonnie D.; Yeatts, Sharon D.; Tamariz, Diego; Ryckborst, Karla (Stroke (1970), 2011)
enrollment in the Albumin in Acute Stroke (ALIAS) Trial was suspended in late 2007 due to a safety concern. We present the safety data of that Trial ("Part 1") and the rationale for the design of Part 2. ALIAS Part 1 was designed to assess whether 25% albumin (ALB) started within 5 hours of stroke onset would confer neuroprotection in subjects with acute ischemic stroke and baseline National Institutes of Health Stroke Scale of ≥ 6. Exclusion criteria included recent or current congestive heart failure, myocardial infarction, or cardiac surgery. The study comprised 2 cohorts: subjects who received thrombolysis and those who did not, each with 1:1 randomization to ALB or placebo. The primary outcome was the National Institutes of Health Stroke Scale and modified Rankin Scales at 90 days. The intended sample size was 1800. four hundred thirty-four subjects were enrolled, and 424 were used in the safety analysis (ALB 207, saline 217). There were 36 deaths within the first 30 days in the ALB group and 21 in the saline group. In contrast, death rates after 30 days were similar by treatment. Large strokes were the predominant cause of early death in both groups. In subjects >83 years of age, 90-day death rates were 2.3-fold higher with ALB than with saline (95% CI, 1.04 to 5.12). Similarly, 90-day deaths in subjects receiving excessive fluids were 2.10-fold greater with ALB than with saline (CI, 1.10 to 3.98). The ALIAS Part 2 Trial, which started in early 2009, was modified as follows to enhance safety: upper age limit of 83 years; requirement for normal baseline serum troponin level; restriction of total intravenous fluids in the first 48 hours to ≤ 4200 mL; mandatory diuretic at 12 to 24 hours; and detailed site retraining. Because of insufficient nonthrombolysed subjects (22%) in Part 1, the 2-cohort design was eliminated. The Data Safety Monitoring Board has reviewed the safety data of Part 2 3 times and has approved continuation of the trial.